Forging the Ideal Educated Girl The Production of Desirable Subjects in Muslim South Asia - Khoja-Moolji, Shenila (Islamic Humanities, 2018)
In Forging the Ideal Educated Girl, Shenila Khoja-Moolji traces the figure of the 'educated girl' to examine the evolving politics of educational reform and development campaigns in colonial India and Pakistan. She challenges the prevailing common sense associated with calls for women's and girls' education and argues that such advocacy is not simply about access to education but, more crucially, concerned with producing ideal Muslim woman-/girl-subjects with specific relationships to the patriarchal family, paid work, Islam, and the nation-state. Thus, discourses on girls'/women's education are sites for the construction of not only gender but also class relations, religion, and the nation.